An In-Depth Analysis of Instructors’ Perceptions of Utilizing ChatGPT in Developing Courses and Learning Materials - Mark Jameson E. Perez (Journal of Technology-Assisted Learning, 2026)
This sequential explanatory research design study determined the instructors’ level of perceptions and efficiency in using ChatGPT as an educational tool for developing courses and learning materials. It also investigated the challenges and limitations that instructors have encountered while utilizing this tool. The study involved 138 respondents, and the five participants were from regular campuses of a state university in Central Luzon who had immersed themselves in the utilization of ChatGPT. The samples of the study signify that they were actively engaged in exploring and integrating AI tools, particularly ChatGPT, in teaching pedagogy. The instruments used in this study were researcher-made questionnaires. The quantitative tool involved indicators of the perceptions of instructors on the usefulness, ease of use, attitudes, impact, and efficiency of the tool in identifying learning, performance, and assessment outcomes. The qualitative instrument was about the difficulties, authenticity and reliability issues, ethical issues and concerns, technical limitations, and strategies to improve the ChatGPT-generated content. The results showed that ChatGPT is a beneficial educational tool; it is user-friendly, especially for seasoned faculty with different levels of technological expertise. However, it was also revealed that ChatGPT does not enhance the critical and analytical thinking of the instructors as they innovate diverse course learning materials. Furthermore, the findings showed that instructors must be responsible users and critically evaluate the generated outputs because they may be inaccurate, vague, or outdated. Its technical limitations affect coherence, complexity, and the context itself. The study recommends conducting training on AI integration in education as it can negatively impact the educational system, productivity, and economic stability.